FEATURES AND PROSPECTS FOR USE OF WIND-POWERED DRIVE ON AGRICULTURAL AIRPLANE - V. P. Asovsky; A. S. Kuzmenko (Научный вестник МГТУ ГА, 2017)
The article deals with the wind-powered drive location and functioning pecularities of agricultural airplane special equipment. The data on the advantages and prospects of the use of the wind-powered drive on agricultural aircraft as well as the experimental and analytical data on discontinuity of the wind stream in the zone of the wind-powered drive installa- and parameters of its operation at aerial spraying on the example of specially equipped An-2 are presented. A mathematical model of a wind propeller in discontinuous wind stream is developed. Software package to comprehensively assess wind-powered drive conditions and performance indicators is generated and tested taking into account experimental data, as well as airplane performance and flight modes. The typical data on the wind propeller and the wind-powered drive in the spraying process are received; specific features of the dynamics at the wind-powered drive turning-on and the wind propeller rotation at zero load are determined and the data on the wind-propeller blades load imbalance at spraying and transient processes are defined. The author made a quantitative estimation of how the standard change of flight parameters and the operation of the aircraft power plant at spraying influence on the factors of wind-powered drive operation and working liquids suppey. The main tendencies, qualitative and quantitative aspects of a wind-powered drive use are defined when performing aerial works and the proposals and recommendations for improving and using it in the future are made. The findings of the work can be used in the wind-powered drive of agricultural airplane special equipment designing and modernization and drilling of the operational and technological procedures of aerial works performance in agriculture and forestry.